SONOGRAPHIC DETERMINATION OF FOETAL SEX - Idrees, Mohammad (Journal of Ayub Medical College Abbottabad, 1996)
In order to determine foetal sex antenatally, 300 patients were examined sonographically over a period of two years (June 1993 - May 1995) using a 3.5 MHz sector probe. Gestational age ranged between 26 - 30 weeks. Foetal scrotum, penis and labia majora were identified to establish the foetal gender. Of 258 ladies who reported back after confinement, diagnosis was correct in 214 (82.9%). There were 111 (43%) males and 103 (40%) females. In 44 (17%) of our cases sex could not be ascertained. Main factors contributing to unsuccessful outcome were breech presentation (38%), multiple gestation (23.8%), oligohydramnios (11.9%), and non-optimal foetal position (26.2%). There were only two false positive results. Foetal hydrocele was noticed in three cases.